Reading the Quran in the Light of Scripture Theories - Bahri, Media Zainul; Fatkhi, Rifqi Muhammad (Ushuluna: Jurnal Ilmu Ushuluddin, 2025)
This article elucidates several theories of scripture to view the Quran as the word of God and as a holy book responded by its readers. By reading scripture, oral and aural, inspirational, deductive and inductive theories, this article has found out that the Quran enters most of these theories. If Smith proposes the theory that scripture is a human activity, then the Quran is one of the most widely received scriptures in the form of various interpretations that greatly influences the emergence of Muslim religious practices. Smith even called the Quran a holy book par excellent. Scripture theories that were born in the context of Christian theology turned out to provide surprising evidence that the holy book in Christianity and Islam had several things in common: similar in terms of revelation, although in different forms, similar in terms of responding to the holy book, and similar in that the holy book had a strong influence on its adherents.